2022
DOI: 10.1038/s41467-022-30103-2
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane stem cell factor protein therapeutics enhance revascularization in ischemia without mast cell activation

Abstract: Stem cell factor (SCF) is a cytokine that regulates hematopoiesis and other biological processes. While clinical treatments using SCF would be highly beneficial, these have been limited by toxicity related to mast cell activation. Transmembrane SCF (tmSCF) has differential activity from soluble SCF and has not been explored as a therapeutic agent. We created novel therapeutics using tmSCF embedded in proteoliposomes or lipid nanodiscs. Mouse models of anaphylaxis and ischemia revealed the tmSCF-based therapies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(72 citation statements)
references
References 57 publications
5
67
0
Order By: Relevance
“…The findings are particularly significant given the rabbit model’s resistance to angiogenesis and longer-term ischemia 28,29 . Finally, we did not observe any signs of mast cell activation on histological analysis, consistent with our prior studies in mice 27 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings are particularly significant given the rabbit model’s resistance to angiogenesis and longer-term ischemia 28,29 . Finally, we did not observe any signs of mast cell activation on histological analysis, consistent with our prior studies in mice 27 .…”
Section: Discussionsupporting
confidence: 92%
“…Managing ischemia in diabetic individuals has presented continuing challenges in the clinical setting, particularly for those undergoing bypass operations or percutaneous procedures 30,31 where diabetic patients have worse outcomes and reduced benefits from therapy and interventions. Our previous work demonstrated that tmSCF nanodiscs enhance revascularization in healthy and diabetic mice 32 . In this work, we evaluated the efficacy of tmSCF embedded in nanodiscs for therapeutic angiogenesis using an optimized rabbit model of hindlimb ischemia with diabetes and hyperlipidemia 28,29 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We also show that GLP-1 (32)(33)(34)(35)(36) improved mitochondrial dynamics and rescued glycolysis mediated by PFKFB3 (6-phosphofructo-2-kinase/ fructose-2,6-bisphosphatase 3). Our findings provide novel insights into the mechanisms underlying the beneficial effects of GLP-1 (32)(33)(34)(35)(36) on diabetic PAD and highlight its potential therapeutic value for nondiabetic patients due to its angiogenic effect independent of insulin regulation.…”
Section: Highlightsmentioning
confidence: 64%
“…Managing ischemia in diabetic individuals has presented continuing challenges in the clinical setting, particularly for those undergoing bypass operations or percutaneous procedures 30,31 where diabetic patients have worse outcomes and reduced bene ts from therapy and interventions. Our previous work demonstrated that tmSCF nanodiscs enhance revascularization in healthy and diabetic mice 32 . In this work, we evaluated the e cacy of tmSCF embedded in nanodiscs for therapeutic angiogenesis using an optimized rabbit model of hindlimb ischemia with diabetes and hyperlipidemia 28,29 .…”
Section: Discussionmentioning
confidence: 96%